Do centennial tree-ring and stable isotope trends of Larix gmelinii (Rupr.) Rupr. indicate increasing water shortage in the Siberian north? - Sidorova, Olga; Siegwolf, Rolf; Saurer, Matthias; Shashkin, Alexander; Knorre, Anastasia; Prokushkin, Anatoliy; Vaganov, Eugene; Kirdyanov, Alexander (2018)
Tree-ring width of Larix gmelinii (Rupr.) Rupr., ratios of stable isotopes of C (δ13C) and O (δ18O) of whole wood and cellulose chronologies were obtained for the northern part of central Siberia (Tura, Russia) for the period 1864-2006. A strong decrease in the isotope ratios of O and C (after atmospheric δ13C corrections) and tree-ring width was observed for the period 1967-2005, while weather station data show a decrease in July precipitation, along with increasing July air temperature and vapor pressure deficit (VPD). Temperature at the end of May and the whole month of June mainly determines tree radial growth and marks the beginning of the vegetation period in this region. A positive correlation between tree-ring width and July precipitation was found for the calibration period 1929-2005. Positive significant correlations between C isotope chronologies and temperatures of June and July were found for whole wood and cellulose and negative relationships with July precipitation. These relationships are strengthened when the likely physiological response of trees to increased CO2 is taken into account (by applying a recently developed δ13C correction). For the O isotope ratios, positive relationships with annual temperature, VPD of July and a negative correlation with annual precipitation were observed. The δ18O in tree rings may reflect annual rather than summer temperatures, due to the late melting of the winter snow and its contribution to the tree water supply in summer. We observed a clear change in the isotope and climate trends after the 1960s, resulting in a drastic change in the relationship between C and O isotope ratios from a negative to a positive correlation. According to isotope fractionation models, this indicates reduced stomatal conductance at a relatively constant photosynthetic rate, as a response of trees to water deficit for the last half century in this permafrost region